ANALISIS KELAYAKAN FINANSIAL USAHA PEMBESARAN IKAN GURAMI DAN IKAN NILA DI KECAMATAN PAGELARAN, KABUPATEN PRINGSEWU - Rahman, Tufiq Arif; Endaryanto, Teguh; Kasymir, Eka (Lampung University, 2023)
The aimed of this research to analyze financial feasibility, the most profitable fish enlargement, and the sensitivity rate of gouramy and nile tilapia fish enlargement. This research was conducted in Pagelaran Sub-District, Pringsewu Regency from February until March 2019 by survey method. The data used are primary and secondary. The samples size of this research were 43 respondents using simple random sampling method. Data analysis were use financial feasibility analysis with five criteria (Gross B / C Ratio, Net B / C Ratio, NVP, IRR, and Payback Periode) and sensitivity analysis. The results showed that (1) the enlargement of gouramy and nile tilapia is financially profitable and feasible to be cultivated, (2) the business of enlarging gouramy is more profitable than nile tilapia, which is shown four values of financial feasibility criteria (Net Present Value (NPV), Internal Rate) of Return (IRR), Gross B / C, and NetB / C) greater, and (3) sensitivity analysis shows the effect of an increase in production costs of 4,39% and a decrease in production of 5,84% in gouramy rearing, namely It is shown that the sensitivity rate of IRR and Net B / C is more than 1, while in the rearing of tilapia with the assumption of an increase in production costs of 4,39% and a decrease in production of 15,35%, it is sensitive to the calculation of business feasibility shown in the sensitivity rate of IRR and Net B / C of one.